Pronunciation in the development of oral expression in children of 5 years in kindergarden Nº 02 María Inmaculada, Abancay - Huamanttica Ayerbe, Cinthia (2020)
Focused on a problem regarding the deficiency of the appropriate oral expression in the pronunciation, intonation and fluency of words, making the application of workshops of verbal games (rhymes, riddles and tongue twisters). Having as a general objective, to demonstrate how verbal games strengthen in the increase of oral expression in 5-year-old children of the Initial Educational Institution No. 02 María Inmaculada de Abancay 2019. The type of research is applicative, the level and design is quasi-experimental, with a single group of pre test and post test, 21 workshops of verbal games were applied more than 1 of pre and post test, conceiving in total 22 workshops applied in a 5-year classroom with a total amount of 26 sample children. The collection of information was through the instrument: checklist, which contains the performances of the National Curriculum of Basic Education (Curriculum of Initial Education), adapted for each dimension of the dependent variable. For the demonstration of the general hypothesis which is, verbal games strengthen significantly in the development of oral expression in children of 5 years of the Initial Educational Institution No. 02 María Immaculada de Abancay 2019. The percentage statistical effects show in the pronunciation dimension in the Pre Test with 77% children are at the start level and in the Post Test with 92% children are at the achievement level. In the intonation dimension of words in the Pre Test with 81% the children are at the start level and in the Post Test with 88% the children are at the achievement level. In the word fluency dimension in the Pre Test with 85% of the children are in the beginning level and in the Post Test with 85% the children are in the achievement level